The Effectiveness of a Classroom-Based Antenatal Yoga Program in Reducing Pregnancy Discomfort Scores - Dewi Susanti; Siti Maisaroh; Galuh Chandra Dewi (Lembaga Publikasi Ilmiah Nusantara, 2026)
Pregnancy-related discomfort may affect maternal physical and psychological well-being and reduce quality of life during pregnancy. Antenatal yoga has been recognized as a complementary non-pharmacological intervention to improve maternal comfort; however, evidence regarding classroom-based antenatal yoga programs in Indonesian settings remains limited. This study aimed to evaluate the effectiveness of a classroom-based antenatal yoga program in reducing discomfort scores during pregnancy. A quasi-experimental pretest-posttest control-group design was conducted with 44 pregnant women in Tangerang City, Indonesia. Participants were assigned to an intervention group (n = 22) and a control group (n = 22). The intervention group received classroom-based antenatal yoga twice weekly for 3 months, comprising 15-minute sessions including breathing exercises, stretching, pregnancy-adapted yoga postures, and relaxation techniques, while the control group received routine antenatal care. Pregnancy discomfort scores in the intervention group decreased from 11.00 ± 6.37 to 6.00 ± 3.59, whereas the control group showed minimal change from 9.59 ± 4.77 to 9.64 ± 4.79. Post-intervention scores were significantly lower in the intervention group (p = 0.007). Classroom-based antenatal yoga effectively reduced pregnancy discomfort and may be integrated into antenatal care services.